Web-Based Asset Management Information Systems in Higher Education - Kusumojati, Putri Pramestiwi; Mediawati, Elis (International Journal of Business, Law, and Education, 2024)
This study aims to determine the Asset Management Information System in Higher Education. The research method used in this study is the SLR (Systematic Literature Review) method. In this study, SLR (Systematic Literature Review) is used to identify, review, evaluate, and interpret previous studies on the Google scholar database with a period of the last 10 years, namely 2013-2023. The results showed that universities do not yet have an internal information system to control their assets. The absence of an asset management information system will have difficulty in tracing asset data. Solutions to overcome existing problems require a web-based asset management information system that can carry out asset management to be more efficient and organized, and make it easier to collect the number of assets, data about assets based on their condition, grouping assets by type, and make it easier to search asset data.